Intergovernmental Diplomacy and Consensus Rhetoric in United Nations Official Discourse (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
Language plays a central role in multilateral diplomacy, particularly within the institutional framework of the United Nations (UN), where decision-making is strongly oriented toward consensus. This article examines the rhetorical and pragmatic mechanisms through which consensus is constructed in UN official discourse. Drawing on theories of politeness, hedging, modality, strategic ambiguity, and speech act theory, the study analyzes how linguistic strategies such as indirectness, impersonality, passive constructions, euphemism, and modal expressions function to minimize conflict and facilitate agreement among sovereign states. The findings demonstrate that UN diplomatic language systematically avoids overt confrontation in favor of generalized, cooperative formulations that enable divergent political positions to coexist within a shared textual framework. The article argues that consensus in UN discourse is not merely a political outcome but a linguistically mediated process shaped by carefully calibrated rhetorical choices.